Frontiers of Quantum Chemistry - Wójcik, Marek J.; Nakatsuji, Hiroshi; Kirtman, Bernard; Ozaki, Yukihiro; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
The purpose of this book is to convey to the worldwide scientific community the rapid and enthusiastic progress of state-of-the-art quantum chemistry. Quantum chemistry continues to grow with remarkable success particularly due to rapid progress in supercomputers. The usefulness of quantum chemistry is almost limitless. Its application covers not only physical chemistry but also organic and inorganic chemistry, physics, and life sciences. This book deals with all of these topics. Frontiers of Quantum Chemistry is closely related to the symposium of the same name held at Kwansei Gakuin University at Nishinomiya, Japan, in November 2015. The book's contributors, however, include not only invited speakers at the symposium but also many other distinguished scientists from wide areas of quantum chemistry around the world.  .
Rigorous and Empirical Approaches to Correlated Single Particle Theories -- Circular Dichroism Spectroscopy with the SAC-CI Methodology: A ChiraSac Study -- Frontiers of Coupled Cluster Chiroptical Response Theory -- Response Theory and Molecular Properties -- Response Properties of Periodic Materials Subjected to External Electric and Magnetic  Fields -- Quantum Chemical Methods for Predicting and Interpreting Second-Order Nonlinear Optical Properties: from Small to Extended p-conjugated Molecules -- Embedding Methods in Quantum Chemistry -- Calculation of Vibrational Spectra of Large Molecules from their Fragments -- Describing Molecules in Motion by Quantum Many-Body Methods -- Relativistic Time-Dependent Density-Functional Theory for Molecular Properties -- Warming Up Density Functional Theory -- Toward a Quantum Chemical Description of Molecular Properties and Chemical Reactions at Extreme Condition of Pressure -- Transition States of Spin-Crossing Reactions from Organometallics to Biomolecular Excited  States -- Electron Communications and Chemical Bonds -- Molecular Dynamics Simulations of Vibrational Spectra of Hydrogen-Bonded Systems -- Nuclear Quantum Effect and H/D Isotope Effect on Hydrogen-Bonded Systems with Path Integral Simulation -- Vibrational Linear and Nonlinear Optical Properties: Theory, Methods and Application -- Ab Initio Molecular Dynamics Study on Photoisomerization Reactions: Applications to Azobenzene and Stilbene -- Density Functional Theoretical Studies on Chemical Enhancement of Surface-Enhanced Raman Spectroscopy in Electrochemical Interfaces -- Quantum Chemistry Studies of Overtones and Combinations.
Keywords: Physical chemistry; Chemistry, Physical and theoretical; Condensed matter; Bioinformatics; Physical Chemistry; Theoretical Chemistry; Condensed Matter Physics; Computational and Systems Biology